An outbreak of an unusual strain of Listeria monocytogenes infection in North-East Scotland - Emmanuel Okpo; Jayne Leith; Alison Smith-Palmer; John Bell; Duncan Parks; Fiona Browning; Lynn Byers; Helen Corrigan; Diana Webster; Anne M. Karcher; Andrew Murray; Tom Storey (Elsevier, 2015)
Summary: Listeria monocytogenes infection is an important cause of illness and hospitalization in vulnerable individuals. In the present study, we describe a community outbreak of Listeria monocytogenes in the North-East region of Scotland, which was epidemiologically, environmentally and microbiologically linked to a local meat product and ready-to-eat product manufacturer. Infected individuals were interviewed, and an environmental investigation was conducted. Clinical and environmental samples were tested by culture, and isolates were typed by fluorescent amplified fragment length polymorphism (fAFLP). Three cases of Listeria monocytogenes were linked geographically, had the same serotype (1/2a) and were indistinguishable by fAFLP type XII.6. The human, food and environmental isolates were of the same serotype and were indistinguishable by molecular typing.This is the first community outbreak of L. monocytogenes reported in Scotland since the current outbreak surveillance was established in 1996. Epidemiological and laboratory evidence indicated poor hand hygiene, unhygienic practices and cross-contamination throughout the manufacturing process of ready-to-eat foods as a possible cause of the outbreak. More stringent control of commercial food establishments that provide ready-to-eat food and the need to advise specifically vulnerable groups, e.g., pregnant women, of the risk of L. monocytogenes in ready-to-eat food is urgently needed. Keywords: Listeria monocytogenes, Outbreak, Foodborne, Community acquired infection, Listeriosis